2020
DOI: 10.1126/sciadv.aaz9360
|View full text |Cite
|
Sign up to set email alerts
|

Integrated proteomics reveals brain-based cerebrospinal fluid biomarkers in asymptomatic and symptomatic Alzheimer’s disease

Abstract: Alzheimer’s disease (AD) lacks protein biomarkers reflective of its diverse underlying pathophysiology, hindering diagnostic and therapeutic advancements. Here, we used integrative proteomics to identify cerebrospinal fluid (CSF) biomarkers representing a wide spectrum of AD pathophysiology. Multiplex mass spectrometry identified ~3500 and ~12,000 proteins in AD CSF and brain, respectively. Network analysis of the brain proteome resolved 44 biologically diverse modules, 15 of which overlapped with the CSF prot… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

33
358
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 235 publications
(397 citation statements)
references
References 77 publications
33
358
6
Order By: Relevance
“…These factors have previously been identified as key regulators in a sporadic Alzheimer’s disease iPSC model ( Meyer et al , 2019 ), in which neurons also showed increase excitability, and increased tau phosphorylation and amyloid-β 1–40 concentrations, which is in line with our observations and interpretation of subtype 1. Finally, proteins increased in subtype 1 also showed enrichment for glucose metabolism, which has been reported in two recent proteomic studies in tissue and in CSF that also observed clusters of proteins associated with glucose metabolism to be involved in Alzheimer’s disease, as well as clusters of synaptic proteins ( Higginbotham et al ., 2019; Johnson et al , 2020 ). In those studies, and our results, glucose metabolism pathways mostly included proteins that were specific for neurons and/or astrocytes.…”
Section: Discussionsupporting
confidence: 65%
“…These factors have previously been identified as key regulators in a sporadic Alzheimer’s disease iPSC model ( Meyer et al , 2019 ), in which neurons also showed increase excitability, and increased tau phosphorylation and amyloid-β 1–40 concentrations, which is in line with our observations and interpretation of subtype 1. Finally, proteins increased in subtype 1 also showed enrichment for glucose metabolism, which has been reported in two recent proteomic studies in tissue and in CSF that also observed clusters of proteins associated with glucose metabolism to be involved in Alzheimer’s disease, as well as clusters of synaptic proteins ( Higginbotham et al ., 2019; Johnson et al , 2020 ). In those studies, and our results, glucose metabolism pathways mostly included proteins that were specific for neurons and/or astrocytes.…”
Section: Discussionsupporting
confidence: 65%
“…NPEPPS digests soluble tau purified from non-pathological human brain but not the tau purified from AD brain [ 72 ], suggesting its role in the clearance of normal tau in a posttranslational modification-sensitive manner. CSF NPEPPS is investigated as a biomarker candidate in AD patients [ 73 ]. Thus, the combination of HSPA1A and NPEPPS in CSF EVs may serve as a potential biomarker in monitoring the conversion of MCI to AD.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are same bioinformatics analysis researches that reported many biomarkers for AD based on the peripheral blood mononuclear cell (PBMC) expression datasets [ 46 , 47 ]. Meanwhile, the currently published relevant papers were most associated with large-scale transcriptome or proteomics analysis in the brain tissues and cerebrospinal fluid samples [ 48 , 49 , 50 ]. The purpose of this study is to select potential biomarkers from GSE database and validate the expression of these DEGs in peripheral human AD samples and both peripheral/central nervous AD and aging mice samples, which could be served as both the early diagnosis biomarkers and potential targeted genes for pathological researches of AD or aging-related neurodegenerative disorders.…”
Section: Discussionmentioning
confidence: 99%